ANALISIS IMPACT KERJASAMA BILATERAL INDONESIA - MALAYSIA DALAM PATROLI TERKOORDINASI KASTAM INDONESIA - MALAYSIA (PATKOR KASTIMA) TERKAIT PEMBERANTASAN PAKAIAN BEKAS IMPOR ILEGAL DI PERAIRAN SELAT MALAKA PERIODE 2014 - 2019 - Rani Permata Sari, (2021)
The smuggling of imported secondhand clothing is one of the illegal activities that is rife in the Malacca Strait. Even though it is the used item, these clothes are still suitable for use and are of good quality at very cheap prices. This happened because of the high demand from our society. Despite the government's ban on this matter, the public seems not think too much about the regulation. Buying and selling used clothing continues to run smoothly and even more enthusiasts. The used clothes come from various countries in the world such as: France, China, United States, Japan, South Korea, Singapore, Malaysia and others. But the most common entry into Indonesia is used clothing from Malaysia, which is smuggled through the Malacca Strait. In 1994, Indonesia and Malaysia created a bilateral cooperation in order to secure the Malacca Strait area from various threats of maritime crime such as smuggling used clothing. In terms of its layout and history, the Malacca Strait is a global trade trajectory that has vital points in the political, economic and security fields. This is what makes this region prone to crime. Threats are not only militaristic, but also including transnational organized crime, threats to the marine environment, illegal commodity trading and even terrorism. This bilateral cooperation was named Patkor Kastima (Indonesian-Malaysian Kastam Coordinated Patrol). The Indonesian side was represented by the Directorate General of Customs and Excise (DJBC) and Malaysia is represent by The Post of Royal Palace in malaysia (JKDM).